(untitled) (Proceedings of Southern Federal University. Philology, 2013)
Firsova E.V. Keywords: speech behaviour, the expectation of strong and weak obligation, the expectation of possible behaviour. This article describes R. Dahrendorf’s classification of social expectations in its extrapolations on the speech behavior of interlocutors. The basis of this classification is the obligation for the members of the society to adhere the norms and rules both on the level of national community and on the level of individual social groups. Speech norms are also heterogeneous in this aspect. R. Dahrendorf’s classification in the context of social expectations in speech allows specifying the degree of obligation for native speakers how to observe speech norms in different communicative situations.